If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -6 = 4y + 4 Reorder the terms: -6 + 5y = 4y + 4 Reorder the terms: -6 + 5y = 4 + 4y Solving -6 + 5y = 4 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. -6 + 5y + -4y = 4 + 4y + -4y Combine like terms: 5y + -4y = 1y -6 + 1y = 4 + 4y + -4y Combine like terms: 4y + -4y = 0 -6 + 1y = 4 + 0 -6 + 1y = 4 Add '6' to each side of the equation. -6 + 6 + 1y = 4 + 6 Combine like terms: -6 + 6 = 0 0 + 1y = 4 + 6 1y = 4 + 6 Combine like terms: 4 + 6 = 10 1y = 10 Divide each side by '1'. y = 10 Simplifying y = 10
| 3x+30=5x | | D=k+p/2 | | 2/3(4x-7)=-3 | | 3k+2k=6+3k | | 2x-3-4x+5=10 | | 8x+33=3-2x | | 9-3c=36 | | (5/-9)(-2/7)(-3) | | 2x+2=4x-11 | | 60+c=-10 | | 6(2x+3)-3x=63 | | 7y*4.6= | | 20-5c=50 | | 3/4m=-2/3 | | 5/-9x-2/7x-3 | | -3x+7+2x=37 | | 2/3m=3/4 | | (x^2-4)(x^2-4)=-5 | | 3x+7+2x=37 | | 2x+3+2=-1 | | 2x=103+x | | -2(4x-5)=38 | | 10=25+.5x | | 11=5(n-9) | | 6(9x+18)=60 | | 3/4m=3/7 | | 6(2y+5)=78 | | x/3-19=5 | | -4+5x=87 | | 4p-3=2p+5 | | 5(18+x)+10(4x)+25x=1420 | | 75-5n=100 |